PERANAN MANTHUQ DAN MAFHUM DALAM MENETAPKAN HUKUM DARI AL- QUR’AN DAN SUNNAH - Ahmad Atabik (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2015)
The article discusses mantuq and mafhum in drawing the laws from Qur’an and Sunnah. The author begins with the understanding of manthuq and mafhum. According to Al-Qatthan (2002: 358) manthuq is a meaning that is indicated by lafadh according to its words, the meaning is based on the spoken letters. On the other hand, mafhum is meaning indicated by lafadh based on other than its sound. The ushuliyyin differentiates mafhum into two kinds, namely: a) mafhum muwafaqah or dilalah nash, meaning the law in accordance with manthuq, and b) mafhum mukhalafah means unspoken meaning which is drawn from manthuq but the opposite. There are dispute among scholars over manthuq and mafhum. Scholars agree on using manthuq as hujjah (proof), but most of them have different opinions about using mafhum as hujjah. They agree on the validity of mafhum muwafaqah as proof (hujjah) except Zahiri schools. However, mafhum mukhalafah is allowed and recognized only by Maliki, Shafi’i and Hanbali. While the Hanafi and his companions refused it